Organic waste-derived pore formers for macroporous ceramics fabrication: a review on synthesis, durability properties and potential applications. - Dele-Afolabi, T.T.; Azmah Hanim, M.A.; Oyekanmi, A.A.; Ansari, M.N.M.; Sikiru, Surajudeen; Ojo-Kupoluyi, O.J. (Elsevier BV, 2024)
Researchers have switched their focus on advancing the exploitation of the cost-effective pore-forming agent (PFA) fabrication method due to the capital-intensive nature of the cutting-edge technologies for the manufacture of macroporous ceramics with tailored porosity. The introduction of synthetic pore formers, however, has raised serious concerns since it poses the risk of increasing the cost, complexity, and turnaround time of this fabrication process. In light of these problems, developing porous ceramics using organic wastes as pore formers is emerging as a popular substitute method for incorporating pores into ceramic matrices. This review discusses the overall performance and critical assessment of macroporous ceramic systems developed using PFAs derived from organic wastes from starch and agricultural wastes. In relation to the requirements and criteria for manufacturing processes, the tremendous potential of these intriguing porous ceramics for energy- and environment-based applications, such as insulation, filtration, energy storage and conversion media, and energy harvesting systems are highlighted. This paper is expected to serve as a guide for producing advanced macroporous ceramics developed from organic waste that have the appropriate pore architectures and properties needed for a range of applications. Finally, this review demonstrates how the development of present and upcoming energy and environmental technologies may benefit from the use of these porous ceramics.